Nutritional Strategies to Mitigate Complications and Improve Long-Term Functionality of Autologous Arteriovenous Fistula Post Ultrasound and DSA Guided Balloon Dilation - Liu, Guangjun; Xu, Yuxiang; Wang, Xuliang; He, Yongchun; Jiang, Hua; Chen, Jianghua (Current topics in nutraceuticals research, 2024)
This prospective cohort study evaluated the efficacy of omega-3 fatty acid supplementation on arteriovenous fistula patency and systemic inflammation in 220 hemodialysis patients undergoing ultrasound and digital subtraction angiography-guided balloon dilation. The participants were randomized into an intervention group receiving 2,000 mg of omega-3 fatty acids daily and a placebo group. The primary outcome measures were arteriovenous fistula patency at 12- and 24-months post-dilation, while secondary outcomes included thrombosis incidence, changes in inflammatory markers (c-reactive protein and interleukin-6), lipid profiles, and health-related quality of life (HRQoL). Results indicated a significant improvement in arteriovenous fistula patency in the omega-3 group at 24 months (80.9 vs. 68.2%, P < 0.05). Additionally, there was a significant reduction in thrombosis rates (7.3 vs. 16.4%, P < 0.05) and inflammatory markers (c-reactive protein and interleukin-6) in the omega-3 group compared to the placebo. Lipid profile analysis showed a decrease in total cholesterol and low-density lipoprotein levels with omega-3 supplementation, with significant changes at 12 months (P < 0.05). HRQoL scores also improved significantly in the omega-3 group at both 12 and 24 months (P < 0.05). These findings suggest that omega-3 fatty acids can enhance arteriovenous fistula functionality and reduce cardiovascular risk factors in hemodialysis patients. And its integration into standard care protocols for patients with arteriovenous fistulas would improve long-term outcomes.